Reflexões sobre a ontologia e a epistemologia da ciência da economia à luz do realismo de Charles S. Peirce: uma abordagem semiótica e pragmatista - Madi, Maria Alejandra Caporale (2022)
The present thesis elaborates the contours of a Science of Economics philosophically informed under the Realism of Charles S. Peirce, considering a semiotic and pragmatist approach. It is proposed a reflection on the relevance of Ontological Indeterminism and Epistemological Fallibilism for a semiotic and pragmatist approach to realistic economic theories. In view of this, there is the assumption of an imbrication between the Epistemology and Ontology of the object of investigation considered in its historical and evolutionary circumstantiality. The first chapter deals with aspects of the Peircean philosophical system and its interrelations between Phenomenology, Ontology, Cosmology and Epistemology. It is considered that, under the action of Chance, a philosophy of the Science of Economics presupposes that Ontological Indeterminism has epistemological implications. In the second chapter, it is addressed how the indeterminist ontology can condition the elaboration of realist economic theories. The ontological assumptions of the modes of being of real — Chance, Existence and Law — require a corresponding epistemology, which implies the development of a methodology in which the three inferential arguments (Abduction, Deduction and Induction) are axial in the logic of investigation. The inferences are studied in an ontological and epistemic perspective that privileges the theory-world dialogue. The aim is to put in question aspects of contemporary methodology in the Science of Economics, in which mathematical, statistical and computational models have a prominent role. In the third chapter, we elaborate the consequences of the cohabitation of Law and Chance in the construction of an Epistemology of Economics whose object of inquiry is complex. By considering an evolutionary perspective, we reflect on the nature of Economic Laws under the impact of Chance and point out that Ontological Indeterminism can condition the predictive reach of realist theories when considering the nature of the object of study. In chapter four, a reflection on the sign-object homology and its implications for practical philosophy is proposed. In view of this, Phenomenology, Ontology and Semiotics are articulated to think about the circulation and action of signs (Icons, Indices and Symbols) in contemporary capitalist markets. This background allows us to conjecture about the pluralism of interpretations and ideology in the Science of Economics. Finally, one can conclude that a realistic economic theory, whose relations among concepts represent real logical relations among the phenomena of experience, can be built on the basis of Peirce's Phenomenology, Ontology, and Logic or Semiotics. The triad thought-sign-action, in a Semiotic and Pragmatist approach to the Science of Economics calls for a knowledge in the future that can condition the scope of the Reasonableness promulgated by Peircean Pragmati(ci)sm. Thus, we assert an articulation between Ontology, Epistemology, and Pragmatist Ethics in a realistic Philosophy of the Science of Economics by recognizing the inseparability of ethical behaviour and true scientific knowledge